Challenges in maintaining treatment services for people who use drugs during the COVID-19 pandemic - Adrian Dunlop; Buddhima Lokuge; Debbie Masters; Marcia Sequeira; Peter Saul; Grace Dunlop; John Ryan; Michelle Hall; Nadine Ezard; Paul Haber; Nicholas Lintzeris; Lisa Maher (BMC, 2020)
Abstract The impact of COVID-19 across health services, including treatment services for people who use drugs, is emerging but likely to have a high impact. Treatment services for people who use drugs provide essential treatment services including opiate agonist treatment and needle syringe programmes alongside other important treatment programmes across all substance types including withdrawal and counselling services. Drug and alcohol hospital consultation-liaison clinicians support emergency departments and other services provided in hospital settings in efficiently managing patients who use drugs and present with other health problems. COVID-19 will impact on staff availability for work due to illness. Patients may require home isolation and quarantine periods. Ensuring ongoing supply of opiate treatment during these periods will require significant changes to how treatment is provided. The use of monthly depot buprenorphine as well as moving from a framework of supervised dosing will be required for patients on sublingual buprenorphine and methadone. Ensuring ready access to take-home naloxone for patients is crucial to reduce overdose risks. Delivery of methadone and buprenorphine to the homes of people with confirmed COVID-19 infections is likely to need to occur to support home isolation. People who use drugs are likely to be more vulnerable during the COVID-19 epidemic, due to poorer health literacy and stigma and discrimination towards this group. People who use drugs may prioritise drug use above other health concerns. Adequate supply of clean injecting equipment is important to prevent outbreaks of blood-borne viruses. Opiate users may misinterpret SARS-CoV2 symptoms as opiate withdrawal and manage this by using opioids. Ensuring people who use drugs have access to drug treatment as well as access to screening and testing for SARS-CoV2 where this is indicated is important.